Sizing agent for fibers and application thereof
By using specific ratios of compounds (A) and acetylene-based compounds (B) as fiber-reinforced composite materials as sizing agents, the problem of difficult to take into account both wetting and adhesion between fiber and matrix resin is achieved, and high bundle collection is achieved and excellent physical properties.
Patent Information
- Application Number
- CN202380052453.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-06-27
- Publication Date
- 2025-02-11
AI Technical Summary
Among the existing fiber-reinforced composite materials, it is difficult to take into account the wetting and adhesion between the fiber and the matrix resin, resulting in poor process passing properties and poor physical properties of the composite material, and the fibers are prone to wool and insufficient bundling properties.
Using a specific ratio of fiber sizing agent containing the compound (A) and acetylene-based compound (B) in a thermosetting resin, thermoplastic resin, rubber, a specific ratio, to improve wetting between the fiber and the matrix resin by uniformly adhering the sizing agent to the fiber tow. properties and adhesiveness.
Excellent wetting and adhesion between the fiber and the matrix resin is achieved, bleaching of the fibers is suppressed, and bundling is improved, thereby obtaining a fiber-reinforced composite material with excellent physical properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a fiber sizing agent and its use, and more particularly to a fiber sizing agent, a fiber bundle using the sizing agent, and a fiber-reinforced composite material. Background Art
[0002] Fiber-reinforced composite materials obtained by reinforcing plastic materials (called matrix resins) with various synthetic fibers are widely used in automotive applications, aerospace applications, sports and leisure applications, general industrial applications, etc. As the fibers used in these composite materials, various inorganic fibers such as carbon fibers, glass fibers, and ceramic fibers, and various organic fibers such as aramid fibers, polyamide fibers, and polyethylene fibers can be cited. These various fibers are usually manufactured in the form of filaments, and then processed into sheet-like intermediate materials called unidirectional prepregs through various high-level processing steps, such as hot melt methods, drum winding methods, etc., or processed by filament winding methods, or processed into fabrics or chopped fiber shapes according to the situation, and used as reinforcing fibers, for example.
[0003] Epoxy resins are widely used as matrix resins for fiber-reinforced composite materials. In addition to epoxy resins, unsaturated polyester resins, vinyl ester resins, acrylic resins, etc. are also used as matrix resins for free radical polymerization.
[0004] In order to improve the mechanical strength of fiber-reinforced composite materials, the wettability or adhesion between the matrix resin and the fiber is important, and sizing agents for improving the wettability and adhesion of the fiber for the above-mentioned epoxy resin and free radical polymerization matrix resin have been proposed (for example, Patent Documents 1 and 2).
[0005] However, the sizing agents described in Patent Documents 1 and 2 improve the wettability and adhesion of the fiber to the epoxy resin and the matrix resin of the free radical polymerization system, respectively, but it is difficult to take both into account and fail to meet the process passability and the physical properties of the final composite material. In addition, the fiber sometimes has a low elongation and a brittle nature. These fibers with the previous sizing agents sometimes produce mechanical friction during the processing process, resulting in fuzzing or causing fiber breakage, insufficient bundling, and other problems.
[0006] Therefore, in the field of fiber-reinforced composite materials, there is a demand for the development of a sizing agent that can improve the wettability between fibers and matrix resins to achieve strong adhesion, suppress the fuzzing of fiber bundles to improve bundling properties, and further have excellent long-term storage stability.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 53-52796
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 06-173170 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In view of the above-mentioned prior art background, an object of the present invention is to provide a fiber sizing agent that improves the wettability of a matrix resin with respect to a fiber bundle, a fiber bundle using the sizing agent, and a fiber-reinforced composite material.
[0013] Means for solving problems
[0014] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that a fiber sizing agent containing a specific compound (A) and a specific compound (B) at a specific ratio can solve the above-mentioned problems.
[0015] That is, the sizing agent for fibers of the present invention includes the following embodiments.
[0016] <1> A sizing agent for fibers, comprising a compound (A) and an acetylene compound (B), wherein the compound (A) is at least one selected from a thermosetting resin (A1), a thermoplastic resin (A2) and a rubber (A3), and the weight ratio of the acetylene compound (B) to the compound (A) ((B) / (A)) is 0.0005 to 0.13.
[0017] <2> As mentioned above <1> The fiber sizing agent, wherein the thermosetting resin (A1) is at least one selected from epoxy resin (A1-1), vinyl ester resin (A1-2) and unsaturated polyester resin (A1-3), the thermoplastic resin (A2) is at least one selected from aromatic polyurethane resin (A2-1), saturated polyester resin (A2-2) and polyolefin resin (A2-3), and the rubber (A3) is at least one selected from silicone rubber (A3-1) and diene rubber (A3-2).
[0018] <3> As mentioned above <1> or <2> The fiber sizing agent further contains a nonionic compound (C), and the weight ratio of the acetylene compound (B) to the nonionic compound (C) ((B) / (C)) is 0.001 to 0.5.
[0019] <4> As mentioned above <3> In the fiber sizing agent, the weight average molecular weight of the nonionic compound (C) is 1,000 to 20,000.
[0020] <5> As mentioned above <1> to <4> The fiber sizing agent described in any one of the preceding claims, wherein the acetylene compound (B) is at least one selected from the group consisting of acetylene alcohol (B1), acetylene diol (B2), a compound (B3) formed by adding alkylene oxide to acetylene alcohol, and a compound (B4) formed by adding alkylene oxide to acetylene diol.
[0021] <6> As mentioned above <5> The fiber sizing agent, wherein the acetylene alcohol (B1) is a compound represented by the following general formula (1), the acetylene diol (B2) is a compound represented by the following general formula (2), the compound (B3) formed by adding alkylene oxide to the acetylene alcohol is a compound represented by the following general formula (3), and the compound (B4) formed by adding alkylene oxide to the acetylene diol is a compound represented by the following general formula (4).
[0022] [Chemical formula 1]
[0023]
[0024] (In formula (1), R 1 and R 2 are each independently an alkyl group having 1 to 8 carbon atoms.
[0025] [Chemical formula 2]
[0026]
[0027] (In formula (2), R 3 , R 4 , R 5 and R 6 are each independently an alkyl group having 1 to 8 carbon atoms.
[0028] [Chemical formula 3]
[0029]
[0030] (In formula (3), R 1 and R 2 Each independently represents an alkyl group having 1 to 8 carbon atoms. 7 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. AO represents an oxyalkylene group having 2 to 4 carbon atoms. n is a number from 1 to 50.
[0031] [Chemical formula 4]
[0032]
[0033] (In formula (4), R 3 , R 4 , R 5 and R 6 Each of R is independently an alkyl group having 1 to 8 carbon atoms.7 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. 7 They may be the same or different. AO represents an oxyalkylene group having 2 to 4 carbon atoms. m and n are independently a number from 1 to 50.
[0034] <7> A fiber bundle with a sizing agent attached thereto, which is <1> to <6> The fiber sizing agent described in any one of the above is attached to a fiber bundle.
[0035] <8> A fiber-reinforced composite material comprising a matrix resin and the above <7> The fiber bundle with sizing agent attached.
[0036] <9> As mentioned above <8> In the fiber-reinforced composite material, the matrix resin is at least one selected from thermosetting resins and thermoplastic resins.
[0037] Effects of the Invention
[0038] The fiber sizing agent of the present invention can uniformly impart sizing agent to the fiber. In addition, excellent wettability and adhesion to the matrix resin can be imparted to the fiber. In addition, fuzz suppression and high bundling properties can be imparted to the fiber. By using the fiber tow of the present invention, a fiber-reinforced composite material with excellent physical properties can be obtained. DETAILED DESCRIPTION
[0039] Each component of the fiber sizing agent of the present invention is described in detail.
[0040] [Compound (A)]
[0041] The fiber sizing agent of the present invention contains a compound (A). The compound (A) is at least one selected from a thermosetting resin (A1), a thermoplastic resin (A2) and a rubber (A3). The compound (A) may be one kind or two or more kinds may be used in combination.
[0042] The reason why the fiber sizing agent of the present invention contains at least one selected from the group consisting of a thermosetting resin (A1), a thermoplastic resin (A2) and a rubber (A3) to improve the wettability of the matrix resin is considered to be as follows: the compound (A) uniformly covers the fiber surface and imparts appropriate polarity to the entire fiber surface, thereby improving the affinity with the matrix resin.
[0043] As the thermosetting resin (A1), in terms of exerting the effects of the present invention, epoxy resin (A1-1), vinyl ester resin (A1-2), unsaturated polyester resin (A1-3) and phenolic resin (A1-4) etc. can be mentioned. Among them, at least one selected from epoxy resin (A1-1), vinyl ester resin (A1-2) and unsaturated polyester resin (A1-3) is preferred. In terms of further exerting the effects of the present invention, at least one selected from epoxy resin (A1-1) and unsaturated polyester resin (A1-3) is more preferred. These resins may be used alone or in combination of two or more.
[0044] As the thermoplastic resin (A2), in terms of exerting the effects of the present invention, at least one selected from an aromatic polyurethane resin (A2-1), a saturated polyester resin (A2-2) and a polyolefin resin (A2-3) is preferred, at least one selected from an aromatic polyurethane resin (A2-1), a saturated polyester resin (A2-2) and a polyolefin resin (A2-3) is more preferred, and in terms of further exerting the effects of the present invention, at least one selected from a saturated polyester resin (A2-2) and a polyolefin resin (A2-3) is further preferred. Two or more of these resins may be used in combination.
[0045] In order to exert the effects of the present invention, the rubber (A3) is preferably at least one selected from silicone rubber (A3-1) and diene rubber (A3-2), and in order to further exert the effects of the present invention, diene rubber (A3-2) is more preferred. Two or more of these resins may be used in combination.
[0046] 〔Epoxy resin (A1-1)〕
[0047] The epoxy resin (A1-1) refers to a compound having two or more reactive epoxy groups in the molecular structure. As for the epoxy resin, the glycidyl ether type obtained from epichlorohydrin and an active hydrogen compound is representative, and other types include glycidyl ester type, glycidyl amine type, alicyclic type, etc. The epoxy resin may be one type or two or more types may be used in combination.
[0048] The epoxy equivalent of the epoxy resin (A1-1) is preferably 100 to 1500 g / eq. If the epoxy equivalent is within the above range, the suppression of the change of the fiber bundle over time and the adhesion to the matrix resin can be taken into account. The upper limit of the epoxy equivalent is more preferably 1000 g / eq, further preferably 800 g / eq, and particularly preferably 700 g / eq. On the other hand, the lower limit of the epoxy equivalent is more preferably 120 g / eq, further preferably 150 g / eq, and particularly preferably 170 g / eq. In addition, for example, it is more preferably 120 g / eq to 1000 g / eq, further preferably 150 g / eq to 800 g / eq, and particularly preferably 170 g / eq to 700 g / eq. It should be noted that the epoxy equivalent refers to the epoxy equivalent according to JIS-K7236.
[0049] In terms of good heat resistance, the weight average molecular weight of the epoxy resin (A1-1) is preferably 100 to 10000. The lower limit of the average molecular weight is more preferably 150, and further preferably 200. On the other hand, the upper limit of the average molecular weight is more preferably 8000, and further preferably 7000. In addition, for example, it is more preferably 150 to 8000, and further preferably 200 to 7000. The weight average molecular weight is a weight average molecular weight based on the method described in the Examples.
[0050] From the viewpoint of improving the wettability of the matrix resin, the epoxy resin (A1-1) is preferably an aromatic epoxy resin having an aromatic ring in its molecular structure.
[0051] As the above-mentioned aromatic epoxy resin, there can be mentioned: polyglycidyl ether compounds of mononuclear polyphenol compounds such as hydroquinone, resorcinol, and catechol; polyglycidyl ether compounds of polynuclear polyphenol compounds such as dihydroxynaphthalene, biphenol, bisphenol F, bisphenol A, phenol novolac, o-cresol novolac, resorcinol novolac, bisphenol F novolac, bisphenol A novolac, dicyclopentadiene-modified phenol, triphenylmethane, and tetraphenylethane; etc.
[0052] From the viewpoint of the effects of the present invention, the compound represented by the following general formula (5) is preferred among these aromatic epoxy resins.
[0053] [Chemical formula 5]
[0054]
[0055] (In formula (5), R 8 , R 9 , R 10 and R 11 are independently a hydrogen atom or a methyl group. )
[0056] p is an integer of 0 to 30, preferably 0 to 20, more preferably 0 to 10, from the viewpoint of improving the wettability of the matrix resin.
[0057] The method for producing the epoxy resin (A1-1) is not particularly limited, and a known method can be used. The epoxy resin is generally a commercially available product, and these commercially available epoxy resins can be used in the sizing agent for carbon fiber of the present invention.
[0058] [Vinyl ester resin (A1-2)]
[0059] The vinyl ester resin (A1-2) is a compound having at least one selected from the group consisting of a vinyl ester group, an acrylate group, and a methacrylate group. One or more vinyl ester resins (A1-2) may be used. It should be noted that the vinyl ester group represents a group represented by "CH2=CHOCO-", the acrylate group represents a group represented by "CH2=CHCOO-", and the methacrylate group represents a group represented by "CH2=CCH3COO-".
[0060] Examples of the vinyl ester resin (A1-2) include alkyl (meth)acrylates, alkoxypolyalkylene glycol (meth)acrylates, benzyl (meth)acrylates, phenoxyethyl (meth)acrylates, 2-hydroxyalkyl (meth)acrylates, dialkylaminoethyl (meth)acrylates, glycidyl (meth)acrylates, 2-methacryloyloxyethyl 2-hydroxypropyl phthalate, polyalkylene glycol di(meth)acrylates, alkanediol di(meth)acrylates, glycerol di(meth)acrylates, 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, bisphenol A (meth)acrylate, alkylene oxide-added bisphenol A (meth)acrylate, bisphenol A diglycidyl ether (meth)acrylate adducts, alkylene oxide-added bisphenol A diglycidyl ether (meth)acrylate adducts. meth)acrylic acid adduct, trimethylolpropane tri(meth)acrylate, glycidyl(meth)acrylate, phenoxyalkyl(meth)acrylate, phenoxypolyalkylene glycol(meth)acrylate, 2-hydroxy-3-phenoxypropanol(meth)acrylate, polyalkylene glycol nonylphenyl ether(meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, neopentyl glycol(meth)acrylate benzoate, alkylene oxide-added trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, pentaerythritol tri(meth)acrylate hexamethylene diisocyanate urethane prepolymer, etc.
[0061] Among these, the vinyl ester resin (A1-2) preferably has at least one selected from an oxyalkylene group and an aryl group in terms of excellent adhesion to the matrix resin, and more preferably contains an aryl group. Specifically, 2-methacryloyloxyethyl 2-hydroxypropyl phthalate, polyalkylene glycol di(meth)acrylate, phthalic acid 2-(meth)acryloyloxyethyl, phthalic acid 2-(meth)acryloyloxyethyl-2-hydroxyethyl, neopentyl glycol (meth)acrylate benzoate, bisphenol A (meth)acrylate, alkylene oxide-added bisphenol A (meth)acrylate, bisphenol A diglycidyl ether (meth)acrylate adduct, alkylene oxide-added bisphenol A diglycidyl ether (meth)acrylate, The acid adduct is further preferably polyalkylene glycol di(meth)acrylate, bisphenol A (meth)acrylate, alkylene oxide-added bisphenol A (meth)acrylate, bisphenol A diglycidyl ether (meth)acrylate adduct, and alkylene oxide-added bisphenol A diglycidyl ether (meth)acrylate adduct; particularly preferably bisphenol A (meth)acrylate, alkylene oxide-added bisphenol A (meth)acrylate, bisphenol A diglycidyl ether (meth)acrylate adduct, and alkylene oxide-added bisphenol A diglycidyl ether (meth)acrylate adduct.
[0062] 〔Unsaturated polyester resin (A1-3)〕
[0063] As for the unsaturated polyester resin (A1-3), there is no particular limitation as long as it is a polyester resin having a carbon-carbon double bond and is a resin other than the above-mentioned vinyl ester resin (A1-2), and examples thereof include unsaturated polyesters obtained by reacting an acid component containing an α,β-unsaturated dicarboxylic acid with an alcohol. Examples of α,β-unsaturated dicarboxylic acids include maleic acid, fumaric acid, itaconic acid, and derivatives thereof such as anhydrides, and two or more of these may be used in combination. In addition, as required, α,β-unsaturated dicarboxylic acids may be used in combination with saturated dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, adipic acid, and sebacic acid as acid components other than α,β-unsaturated dicarboxylic acids, and derivatives thereof such as anhydrides. Examples of the alcohol include aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,2-propylene glycol, 1,2-butanediol, 1,3-butanediol, and 1,4-butanediol; alicyclic diols such as cyclopentanediol and cyclohexanediol; aromatic diols such as hydrogenated bisphenol A, bisphenol A propylene oxide (1 to 100 mol) adducts, and benzyl alcohol; and polyols such as trimethylolpropane and pentaerythritol. Two or more of these may be used in combination.
[0064] Among the unsaturated polyester resins (A1-3), aromatic unsaturated polyester resins are preferred in order to have excellent adhesion to the matrix resin. Among the aromatic unsaturated polyester resins, more preferred are condensates of fumaric acid or maleic acid and an ethylene oxide (hereinafter referred to as EO) adduct of bisphenol A, condensates of fumaric acid or maleic acid and a propylene oxide (hereinafter referred to as PO) adduct of bisphenol A, and condensates of fumaric acid or maleic acid and EO and PO adducts of bisphenol A (EO and PO additions may be random or block).
[0065] In terms of good heat resistance, the weight average molecular weight of the unsaturated polyester resin (A1-3) is preferably 1000 to 12000. The upper limit of the weight average molecular weight is more preferably 8000, and further preferably 7000. On the other hand, the lower limit of the weight average molecular weight is more preferably 1500, and further preferably 2000. In addition, for example, it is more preferably 1500 to 8000, and further preferably 2000 to 7000. The acid value is preferably 5 or less. The weight average molecular weight is a molecular weight based on the method described in the Examples.
[0066] [Phenolic resin (A1-4)]
[0067] As phenolic resin, for example, resins obtained by condensation of phenols such as phenol, cresol, xylenol, tert-butylphenol, nonylphenol, cashew nut oil, lignin, resorcinol, catechol and aldehydes such as formaldehyde, acetaldehyde and furfural can be mentioned, for example, novolac resin, resol phenolic resin, etc. Novolac resin can be obtained by reacting phenol and formaldehyde in equal amounts or under conditions in which phenol is excessive in the presence of an acid catalyst such as oxalic acid. Resol phenolic resin can be obtained by reacting phenol and formaldehyde in equal amounts or under conditions in which formaldehyde is excessive in the presence of an alkaline catalyst such as sodium hydroxide, ammonia or an organic amine.
[0068] [Aromatic polyurethane resin (A2-1)]
[0069] The aromatic polyurethane resin (A2-1) is a resin obtainable by a reaction of polyisocyanates, polyols, and, if necessary, a chain extender, wherein at least one of the polyisocyanates and the polyols contains an aromatic compound.
[0070] Examples of polyisocyanates include aliphatic diisocyanates such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate, alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate and isophorone diisocyanate, aromatic diisocyanates such as phenylene diisocyanate, toluene diisocyanate and diphenylmethane-4,4'-diisocyanate, aromatic aliphatic diisocyanates such as xylylene diisocyanate, etc. As polyisocyanates, compounds having an alkyl group (e.g., methyl group) substituted on the main chain or ring may also be used.
[0071] Examples of the polyols include polyester diols (polyester diols obtained from aliphatic dicarboxylic acid components having 4 to 12 carbon atoms, such as fumaric acid, maleic acid, itaconic acid, succinic acid, adipic acid, azelaic acid, and sebacic acid; aromatic dicarboxylic acid components, such as phthalic acid, terephthalic acid, isophthalic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, diphenyl dicarboxylic acid, diphenoxyethane dicarboxylic acid, and phthalic anhydride; C2-12 aliphatic diol components, such as ethylene glycol, propylene glycol, butanediol, and neopentyl glycol; and lactone components having 4 to 12 carbon atoms, such as ε-caprolactone), polyether diols (polyethylene glycol, polypropylene glycol, polyoxyethylene / polyoxypropylene block copolymers, polyoxytetramethylene glycol, bisphenol A-alkylene oxide adducts, and the like), polyester ether diols (polyester diols using the above-mentioned polyether diols as part of the diol components), and the like.
[0072] In addition, as chain extenders, diamines can be mentioned in addition to alkylene glycols having 2 to 10 carbon atoms such as ethylene glycol and propylene glycol. Examples of diamines include aliphatic diamines such as linear or branched alkylene diamines having about 2 to 10 carbon atoms such as ethylenediamine, trimethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, trimethylhexamethylenediamine, 1,7-diaminoheptane, and 1,8-diaminooctane, linear or branched polyalkylene polyamines such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and dipropylenetriamine; alicyclic diamines such as isophoronediamine, bis(4-amino-3-methylcyclohexyl)methane, and bis(aminomethyl)cyclohexane; and aromatic diamines such as phenylenediamine, xylylenediamine, and diaminodiphenylmethane.
[0073] Among the aromatic polyurethane resins (A2-1), aromatic polyester-based polyurethane resins are more preferred in order to achieve both heat resistance and adhesion to the matrix resin.
[0074] [Saturated polyester resin (A2-2)]
[0075] Examples of the saturated polyester resin (A2-2) include aliphatic polyester resins and aromatic polyester resins. The saturated polyester resin is preferably a polyalkylene arylate resin or an aromatic polyester resin, and more preferably an aromatic polyester resin, in order to achieve both heat resistance and adhesion to the matrix resin.
[0076] Examples of the aromatic polyester resin include: poly(alkylene terephthalate) (PET), poly(butylene terephthalate) (PBT), etc.; poly(alkylene terephthalate) (e.g., polyethylene naphthalate) (e.g., 1,4-cyclohexyl dimethanol terephthalate (PCT)), etc. The aromatic polyester resin may be a copolyester containing an alkylene arylate unit as a main component (e.g., 50% by weight or more), and examples of the copolymer component include alkylene glycols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butanediol, and hexanediol; polyoxyalkylene glycols having 2 to 4 carbon atoms; asymmetric aromatic dicarboxylic acids, such as phthalic acid and isophthalic acid, or their anhydrides; and aliphatic dicarboxylic acids, such as adipic acid. Furthermore, a small amount of polyol and / or polycarboxylic acid may be used to introduce a branched chain structure into the linear polyester.
[0077] Furthermore, a modified polyester-based resin modified with a modifying compound (for example, an aromatic polyester resin having at least one selected from an amino group and an oxyalkylene group) may also be used. Examples of the modifying compound include polyamines (aliphatic diamines such as linear or branched alkylenediamines having about 2 to 10 carbon atoms such as ethylenediamine, trimethylenediamine, propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, trimethylhexamethylenediamine, 1,7-diaminoheptane, 1,8-diaminooctane, etc.; alicyclic diamines such as isophoronediamine, bis(4-amino-3-methylcyclohexyl)methane, bis(aminomethyl)cyclohexane, etc.; aromatic diamines such as phenylenediamine, xylylenediamine, diaminodiphenylmethane, etc.), polyols (such as (poly)oxyethylene glycol, (poly)oxytrimethylene glycol, (poly)oxypropylene glycol, (poly)oxytetramethylene glycol, etc.; (poly)oxyalkylene glycols having 2 to 4 carbon atoms, etc.), and the like. The modification can be carried out, for example, by mixing the polyester resin with the modifying compound under heating and utilizing amidation, esterification or transesterification reaction.
[0078] In terms of good heat resistance, the weight average molecular weight of the saturated polyester resin (A2-2) is preferably 3000 to 20000. The upper limit of the weight average molecular weight is more preferably 19000, and further preferably 18000. On the other hand, the lower limit of the weight average molecular weight is more preferably 6000, and further preferably 7000. In addition, for example, it is more preferably 6000 to 19000, and further preferably 7000 to 18000. The weight average molecular weight is a molecular weight based on the method described in the Examples.
[0079] [Polyolefin resin (A2-3)]
[0080] Examples of the polyolefin resin (A2-3) include copolymers of olefin monomers and monomers such as unsaturated carboxylic acids copolymerizable with the olefin monomers, and can be produced by a known method. The polyolefin resin may be a random copolymer obtained by copolymerizing an olefin monomer with an unsaturated carboxylic acid, or a graft copolymer obtained by grafting an unsaturated carboxylic acid onto an olefin monomer. One or more polyolefin resins may be used.
[0081] As the olefin monomer, for example, ethylene, propylene, 1-butene, etc. can be mentioned. These can be used alone or in combination of two or more. As the monomer copolymerizable with the olefin monomer, for example, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, fumaric acid, etc. can be mentioned. These can be used alone or in combination of two or more.
[0082] With regard to the copolymerization ratio of the above-mentioned olefin monomer and the monomer copolymerizable with the olefin monomer, in terms of improving the adhesion with the matrix resin, when the total weight of the copolymer is 100 weight %, it is preferred that the olefin monomer is 80 to 99.5 weight % and the monomer copolymerizable with the olefin monomer is 0.5 to 20 weight %, more preferably that the olefin monomer is 90 to 99 weight % and the monomer copolymerizable with the olefin monomer is 1 to 10 weight %, and particularly preferably that the olefin monomer is 95 to 98 weight % and the monomer copolymerizable with the olefin monomer is 2 to 5 weight %.
[0083] It should be noted that, in terms of improving the storage stability of the emulsion, it is preferred to neutralize the modified groups such as carboxyl groups introduced by copolymerization with a basic compound for the polyolefin resin (A2-3). Examples of the basic compound include metal salts such as sodium hydroxide and potassium hydroxide; ammonia; and amines such as laurylamine, ethylenediamine, trimethylamine, dimethylethanolamine, dibutylethanolamine, monoethanolamine, diethanolamine, triethanolamine, monopropanolamine, dipropanolamine, and monobutanolamine. Among these, amines are more preferred, and diethanolamine is particularly preferred.
[0084] The weight average molecular weight of the polyolefin resin (A2-3) is preferably 5,000 to 200,000 in terms of good heat resistance. The upper limit of the weight average molecular weight is more preferably 150,000, and further preferably 130,000. On the other hand, the lower limit of the weight average molecular weight is more preferably 6,000, and further preferably 7,000. In addition, for example, it is more preferably 6,000 to 150,000, and further preferably 7,000 to 130,000. The weight average molecular weight is a molecular weight based on the method described in the Examples.
[0085] 〔Silicone rubber (A3-1)〕
[0086] Examples of the silicone rubber include addition-type silicone resins, self-crosslinking silicone resins, silicone rubber film-forming silicone resin components, and silicone rubber powders, and silicone rubber that forms a film by heating, reaction, etc. is preferred. The silicone rubber may be used alone or in combination of two or more.
[0087] Examples of the addition type silicone resin include room temperature curing type silicone rubber (RTV silicone rubber), low temperature curing type silicone rubber (LTV silicone rubber), silicone resin components of an O / W type emulsion obtained by emulsifying reactive silicone with an emulsifier, etc. Among these, in order to further demonstrate the effects of the present invention, an aqueous dispersion of a silicone resin obtained by emulsifying room temperature curing type silicone rubber (RTV silicone rubber) or reactive silicone is preferred, and a silicone rubber coating film can be formed by drying the aqueous dispersion.
[0088] [Diene rubber (A3-2)]
[0089] The diene rubber (A3-2) is not particularly limited as long as it is a polymer containing a polymerizable monomer having a conjugated diene structure as a structural unit. Examples of the polymerizable monomer having a conjugated diene structure include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, and 1,3-pentadiene.
[0090] Specific examples of the diene rubber (A3-1) include butadiene polymers, isoprene polymers, styrene-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-isoprene copolymers, acrylonitrile-butadiene-isoprene copolymers, methacrylonitrile-butadiene copolymers, methacrylonitrile-isoprene copolymers, methacrylonitrile-butadiene-isoprene copolymers, acrylonitrile-methacrylonitrile-butadiene copolymers, acrylonitrile-butadiene-methyl acrylate copolymers, acrylonitrile-butadiene-acrylic acid copolymers, acrylonitrile-butadiene-methacrylic acid copolymers, acrylonitrile-butadiene-n-butyl acrylate copolymers, acrylonitrile-butadiene-n-butyl acrylate-mono-n-butyl itaconate copolymers, etc. Among them, styrene-butadiene copolymers are preferred in terms of excellent heat resistance. The diene rubber may be an aqueous dispersion or a substance that can form a film by drying the aqueous dispersion.
[0091] [Acetylene compounds (B)]
[0092] The sizing agent for carbon fiber of the present invention contains an acetylene compound (B). It is presumed that the combined use of the compound (A) and the acetylene compound (B) reduces the surface tension and increases the affinity between the matrix resin and the fiber surface, thereby improving the wettability of the matrix resin.
[0093] It is speculated that when other surfactants are used only without using the acetylene compound (B), although there is an effect of reducing the surface tension when only the compound (A) is used, the affinity between the matrix resin and the fiber surface is insufficient, and therefore the wettability of the matrix resin is not sufficient.
[0094] It should be noted that the acetylene compound refers to a compound having a hydrophilic group such as an acetylene group and a hydroxyl group in its molecular structure. The acetylene compound (B) may be used alone or in combination of two or more.
[0095] The acetylene compound (B) is preferably an acetylene surfactant, and more preferably at least one selected from acetylene alcohol (B1), acetylene glycol (B2), a compound (B3) in which alkylene oxide is added to acetylene alcohol, and a compound (B4) in which alkylene oxide is added to acetylene glycol. Among these, the compound (B3) in which alkylene oxide is added to acetylene alcohol and the compound (B4) in which alkylene oxide is added to acetylene glycol are preferred, and the compound (B4) in which alkylene oxide is added to acetylene glycol is further preferred.
[0096] Acetylene alcohol (B1) is a compound having an acetylene group and one hydroxyl group in its molecular structure.
[0097] The acetylene alcohol (B1) is preferably a compound represented by the above general formula (1).
[0098] Acetylene glycol (B2) is a compound having an acetylene group and two hydroxyl groups in its molecular structure.
[0099] The acetylene glycol (B2) is preferably a compound represented by the above general formula (2).
[0100] The compound (B3) in which alkylene oxide is added to acetylene alcohol is a compound in which alkylene oxide is added to a hydroxyl group of acetylene alcohol.
[0101] The compound (B3) obtained by adding alkylene oxide to acetylene alcohol is preferably a compound represented by the above general formula (3).
[0102] The compound (B4) in which alkylene oxide is added to acetylene glycol refers to a compound in which alkylene oxide is added to at least one of the hydroxyl groups of acetylene glycol.
[0103] The compound (B4) obtained by adding alkylene oxide to acetylene glycol is preferably a compound represented by the above general formula (4).
[0104] In formula (1) and formula (3), R 1 and R 2 Each independently represents an alkyl group having 1 to 8 carbon atoms. The alkyl group may be straight chain or branched. The alkyl group preferably has 1 to 7 carbon atoms, more preferably 1 to 6 carbon atoms, and further preferably 1 to 5 carbon atoms.
[0105] In formula (2) and formula (4), R 3 , R 4 , R 5 and R 6 Each independently represents an alkyl group having 1 to 8 carbon atoms. The alkyl group may be straight chain or branched. The alkyl group preferably has 1 to 7 carbon atoms, more preferably 1 to 6 carbon atoms, and further preferably 1 to 5 carbon atoms.
[0106] In formula (3) and formula (4), R 7 It is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. The alkyl group preferably has 1 to 4 carbon atoms, more preferably 1 to 3 carbon atoms, and further preferably 1 to 2 carbon atoms.
[0107] In formula (3) and formula (4), AO represents an oxyalkylene group having 2 to 4 carbon atoms. That is, it represents an oxyethylene group, an oxypropylene group, or an oxybutylene group. As the oxyalkylene group, an oxyethylene group and an oxypropylene group are preferred, and an oxyethylene group is more preferred. Composition (AO) n or (AO) m The AO may be one type or two or more types. In the case of two or more types, any of a block adduct, an alternating adduct, and a random adduct may be used.
[0108] In formula (3), n is a number of 1 to 50. n is preferably 1 to 45, more preferably 1 to 40, and even more preferably 1 to 35.
[0109] In formula (4), m and n are each independently a number of 1 to 50. m and n are each independently preferably 1 to 45, more preferably 1 to 40, and even more preferably 1 to 35.
[0110] From the viewpoint of emulsification, the HLB of the acetylene compound (B) is preferably 4 to 25. The upper limit of the HLB is more preferably 20, and further preferably 18. On the other hand, the lower limit of the HLB is more preferably 5, and further preferably 6. The HLB in the present invention can be experimentally determined by the atlas method (Japanese: アトラス method) advocated by Griffin et al.
[0111] The acetylene compound (B) is a known compound and can be easily produced by a known method. For example, such a compound can be obtained by a method called Reppe reaction, which is a method of reacting acetylene and a ketone or an aldehyde under pressure in the presence of a catalyst such as a base or a metal compound.
[0112] The compound (B3) or compound (B4) can be obtained by addition polymerization of acetylene alcohol (B1) or acetylene diol (B2) with an alkylene oxide (eg, ethylene oxide and / or propylene oxide) in the presence of a catalyst such as an alkali or a metal compound.
[0113] [Nonionic compounds (C)]
[0114] In order to improve the wettability of the matrix resin, the fiber sizing agent of the present invention preferably contains a nonionic compound (C). The nonionic compound (C) is a compound other than the above-mentioned compound (A) and the above-mentioned acetylene compound (B), and is preferably a nonionic surfactant.
[0115] Examples of the compound (C) include polyoxyalkylene alkyl ethers and polyoxyalkylene alkenyl ethers such as polyoxyalkylene oleyl ether; polyoxyalkylene alkyl phenyl ethers such as polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, and polyoxyethylene dodecylphenyl ether; polyoxyalkylene alkyl aryl phenyl ethers such as polyoxyethylene tristyryl phenyl ether, polyoxyethylene distyryl phenyl ether, polyoxyethylene styryl phenyl ether, polyoxyethylene tribenzyl phenyl ether, polyoxyethylene dibenzyl phenyl ether, and polyoxyethylene benzyl phenyl ether; polyoxyethylene monolaurate, polyoxyethylene monooleate, polyoxyethylene monostearate, polyoxyethylene monomyristate, polyoxyethylene dilaurate, polyoxyethylene dioleate, polyoxyethylene Polyoxyalkylene fatty acid esters such as ethylene dimyristate and polyoxyethylene distearate; sorbitan esters such as sorbitan monopalmitate and sorbitan monooleate; polyoxyalkylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monostearate and polyoxyethylene sorbitan monooleate; glycerol fatty acid esters such as glycerol monostearate, glycerol monolaurate and glycerol monopalmitate; polyoxyalkylene sorbitol fatty acid esters; sucrose fatty acid esters; polyoxyalkylene castor oil ethers such as polyoxyethylene castor oil ether; polyoxyalkylene hydrogenated castor oil ethers such as polyoxyethylene hydrogenated castor oil ether; oxyethylene-oxypropylene block or random copolymers; terminal sucrose ethers of oxyethylene-oxypropylene block or random copolymers; etc. In terms of good emulsification, compound (C) is preferably a surfactant.
[0116] From the viewpoint of exerting the effects of the present invention, the weight average molecular weight of the compound (C) is preferably 1000 to 20000. The upper limit of the weight average molecular weight is more preferably 18000, further preferably 17000, and particularly preferably 16000. On the other hand, the lower limit of the weight average molecular weight is more preferably 1500, further preferably 1800, and particularly preferably 2000. In addition, for example, it is more preferably 1500 to 18000, further preferably 1800 to 17000, and particularly preferably 2000 to 16000. The weight average molecular weight is a molecular weight based on the method described in the Examples.
[0117] From the viewpoint of exerting the effects of the present invention, the oxyethylene-oxypropylene block or random copolymer is preferably a block copolymer.
[0118] The average number of moles of oxyethylene groups constituting the oxyethylene-oxypropylene block or random copolymer is preferably 10 to 500 from the viewpoint of exerting the effects of the present invention. The upper limit of the average number of moles of oxyethylene groups is more preferably 450, and further preferably 400. On the other hand, the lower limit of the average number of moles of oxyethylene groups is more preferably 30, and further preferably 50. In addition, for example, it is more preferably 30 to 450, and further preferably 50 to 400.
[0119] Regarding the oxyethylene-oxypropylene block or random copolymer, from the viewpoint of exerting the effect of the present invention, the average number of moles of oxypropylene added is preferably 1 to 100. The upper limit of the average number of moles added is more preferably 80, further preferably 70, and particularly preferably 60. On the other hand, the lower limit of the average number of moles added is more preferably 5, further preferably 10, and particularly preferably 15. In addition, for example, it is more preferably 5 to 80, further preferably 10 to 70, and particularly preferably 15 to 60.
[0120] 〔Fiber sizing agent〕
[0121] The fiber sizing agent of the present invention contains a compound (A) and an acetylene compound (B), wherein the weight ratio of the acetylene compound (B) to the compound (A) ((B) / (A)) is 0.0005 to 0.13. It should be noted that the weight of the compound (A) and the acetylene compound (B) refers to the weight of each component in the non-volatile matter contained in the sizing agent of the present invention.
[0122] The reason why the wettability of the matrix resin can be improved by containing the compound (A) and the acetylene compound (B) at a specific ratio is considered to be that the compatibility between the compound (A) and the acetylene compound (B) is improved. If the ((B) / (A)) is less than 0.0005, the wettability of the matrix resin is insufficient, and if it exceeds 0.13, the adhesion to the matrix resin is insufficient.
[0123] From the viewpoint of improving the wettability of the matrix resin, the upper limit of ((B) / (A)) is preferably 0.125, more preferably 0.12, further preferably 0.115, particularly preferably 0.11, and most preferably 0.10. On the other hand, the lower limit of ((B) / (A)) is preferably 0.001, more preferably 0.005, further preferably 0.007, particularly preferably 0.01, and most preferably 0.012. For example, it is preferably 0.001 to 0.125, more preferably 0.005 to 0.12, and further preferably 0.007 to 0.115.
[0124] When the fiber sizing agent of the present invention contains a nonionic compound (C), the weight ratio of the acetylene compound (B) to the nonionic compound (C) ((B) / (C)) is preferably 0.001 to 0.5 from the viewpoint of improving the adhesion to the matrix resin. It should be noted that the weight of the acetylene compound (B) and the nonionic compound (C) refers to the weight of each component in the nonvolatile matter contained in the sizing agent of the present invention.
[0125] The upper limit of the weight ratio is more preferably 0.4, further preferably 0.3, and particularly preferably 0.2. On the other hand, the lower limit of the weight ratio is more preferably 0.02, further preferably 0.03, and particularly preferably 0.05. In addition, for example, it is more preferably 0.02 to 0.4, and further preferably 0.03 to 0.3.
[0126] When the fiber sizing agent of the present invention contains a nonionic compound (C), the weight ratio of the acetylene compound (B) to the total of the compound (A) and the nonionic compound (C) ((B) / ((A)+(C))) is preferably 0.005 to 0.5 from the viewpoint of wettability and adhesion to the matrix resin. It should be noted that the weight of the compound (A), the acetylene compound (B) and the nonionic compound (C) refers to the weight of each component in the nonvolatile matter contained in the sizing agent of the present invention.
[0127] The upper limit of the weight ratio is more preferably 0.4, further preferably 0.3, and particularly preferably 0.2. On the other hand, the lower limit of the weight ratio is more preferably 0.007, further preferably 0.009, and particularly preferably 0.01. In addition, for example, it is more preferably 0.007 to 0.4, further preferably 0.009 to 0.3, and particularly preferably 0.01 to 0.2.
[0128] In terms of bundling and adhesion, the weight ratio of compound (A) in the non-volatile matter of the fiber sizing agent of the present invention is preferably 20% to 99% by weight. The upper limit of the weight ratio is more preferably 98% by weight, further preferably 97% by weight, and particularly preferably 95% by weight. On the other hand, the lower limit of the weight ratio is more preferably 25% by weight, further preferably 30% by weight, particularly preferably 40% by weight, and most preferably 50% by weight. In addition, for example, it is more preferably 25% to 98% by weight, further preferably 30% to 97% by weight, and particularly preferably 40% to 95% by weight.
[0129] In terms of the wettability with the matrix resin, the weight ratio of the acetylene-based compound (B) in the non-volatile matter of the sizing agent for the fiber of the present invention is preferably 0.05% by weight to 10% by weight. The upper limit of this weight ratio is more preferably 9% by weight, further preferably 8% by weight, and particularly preferably 7% by weight. On the other hand, the lower limit of this weight ratio is more preferably 0.06% by weight, further preferably 0.08% by weight, and particularly preferably 0.1% by weight. Additionally, for example, it is more preferably 0.06% by weight to 9% by weight, further preferably 0.08% by weight to 8% by weight, and particularly preferably 0.1% by weight to 7% by weight.
[0130] There is no particular limitation on the method for manufacturing the sizing agent of the present invention, and known methods can be employed. Examples include: a method of putting each component constituting the sizing agent into water under stirring to form an aqueous solution, emulsion, or aqueous dispersion; a method of forming an aqueous solution, emulsion, or aqueous dispersion when manufacturing each component constituting the sizing agent; a method of emulsifying or dispersing each component constituting the sizing agent by putting them into water containing a surfactant under stirring; a method of mixing each component constituting the sizing agent with a pre-emulsified and dispersed emulsion dispersion; a method of mixing each component constituting the sizing agent, heating the resulting mixture to above the softening point, and gradually adding water while applying mechanical shear force using a homogenizer, homogeneous mixer, ball mill, etc. to perform phase inversion emulsification; a method of mixing the pre-emulsified and dispersed emulsion dispersion in the oiling bath (Japanese: 給油浴) for applying the sizing agent, etc.
[0131] Regarding the sizing agent of the present invention, it is preferably self-emulsified and / or emulsified and dispersed in water. When the sizing agent is self-emulsified and / or emulsified and dispersed in water, its average particle size is not particularly limited. From the perspective of storage stability, it is preferably 10 μm or less, more preferably 0.01 to 1 μm, and further preferably 0.01 to 0.5 μm. It should be noted that the average particle size in the present invention refers to the arithmetic average diameter measured by a laser diffraction / scattering particle size distribution measuring device (LA-920 manufactured by Horiba).
[0132] 〔Fiber tow〕
[0133] The fiber tow of the present invention is a material obtained by attaching the above-mentioned sizing agent for the fiber to a raw material synthetic fiber tow, and is suitably used as a reinforcing fiber for reinforcing a thermosetting resin or a thermoplastic matrix resin.
[0134] The manufacturing method of the fiber tow of the present invention is a manufacturing method including a sizing treatment step of attaching the above-mentioned sizing agent for the fiber to a raw material synthetic fiber tow and drying the obtained attachment.
[0135] The method for attaching the fiber sizing agent to the raw synthetic fiber bundle to obtain the attached product is not particularly limited, and the fiber sizing agent may be attached to the raw synthetic fiber bundle by a rubber roller method, a roller dipping method, a spray method, or other known methods. Among these methods, the roller dipping method is preferred because it can evenly attach the fiber sizing agent to the raw synthetic fiber bundle.
[0136] The method for drying the obtained adhered matter is not particularly limited, and for example, the adhered matter may be dried by heating with a heating roll, hot air, a hot plate, or the like.
[0137] It should be noted that when the fiber sizing agent of the present invention is attached to the raw synthetic fiber bundle, all the constituent components of the fiber sizing agent may be mixed before attachment, or the constituent components may be separated into two or more stages for attachment. In addition, within the scope that does not hinder the effect of the present invention, thermosetting resins such as epoxy resins, vinyl ester resins, unsaturated polyester resins and phenolic resins, and thermoplastic resins such as polyolefin resins, nylon resins, polycarbonate resins, polyester resins, polyacetal resins, ABS resins, phenoxy resins, polymethyl methacrylate resins, polyphenylene sulfide resins, polyetherimide resins and polyetherketone resins may be attached to the raw synthetic fiber bundle.
[0138] The fiber tow of the present invention can be used as reinforcing fiber of a composite material having various thermosetting resins or various thermoplastic resins as a matrix resin, and can be used in the form of a continuous fiber or in the form of being cut into a predetermined length.
[0139] The amount of nonvolatile matter of the fiber sizing agent attached to the raw synthetic fiber tow can be appropriately selected as long as it is the necessary amount for the synthetic fiber tow to have the desired function, and its attachment amount is preferably 0.1 to 20% by weight relative to the raw synthetic fiber tow. For a fiber tow in the state of continuous fibers, its attachment amount is more preferably 0.1 to 10% by weight relative to the raw synthetic fiber tow, and more preferably 0.5 to 5% by weight. In addition, for a tow cut to a specified length, it is more preferably 0.5 to 20% by weight, and more preferably 1 to 10% by weight.
[0140] If the amount of the fiber sizing agent attached is small, it is difficult to obtain the effect of the present invention related to wettability with the matrix resin, and the bundling of the synthetic fiber bundle may be insufficient, and the handling property may be poor. In addition, if the amount of the fiber sizing agent attached is too large, the synthetic fiber bundle may become too rigid, and the resin impregnation property may be poor during composite molding, which is not preferred.
[0141] As synthetic fibers of the (raw material) synthetic fiber tow to which the fiber sizing agent of the present invention is applicable, various inorganic fibers such as carbon fibers, glass fibers, and ceramic fibers, and various organic fibers such as aramid fibers, polyethylene fibers, polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, polyarylate fibers, polyacetal fibers, PBO fibers, polyphenylene sulfide fibers, and polyketone fibers can be cited. From the viewpoint of the physical properties of the obtained fiber-reinforced composite material, it is preferred to select at least one of carbon fibers, aramid fibers, polyethylene fibers, polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, polyarylate fibers, polyacetal fibers, PBO fibers, polyphenylene sulfide fibers, and polyketone fibers, and carbon fibers are more preferred.
[0142] 〔Fiber-reinforced composite materials〕
[0143] The fiber-reinforced composite material of the present invention contains a thermosetting matrix resin or a thermoplastic matrix resin and the above-mentioned fiber bundle. The fiber bundle is treated with the fiber sizing agent of the present invention, so that the affinity with the fiber bundle and the thermoplastic matrix resin is good, and the fiber-reinforced composite material with excellent adhesion is obtained.
[0144] The fiber reinforced composite material of the present invention contains a matrix resin and the above-mentioned fiber bundle. The fiber bundle is treated with the sizing agent of the present invention, and the sizing agent is uniformly attached, and has good affinity with the fiber bundle and the matrix resin, thereby becoming a fiber reinforced composite material with excellent adhesion. In addition, the thermal decomposition of the sizing agent during high temperature treatment can be suppressed, and the adhesion hindrance with the matrix resin caused by thermal decomposition can be suppressed. Here, the matrix resin refers to a matrix resin containing a thermosetting resin or a thermoplastic resin, and may contain one or more than two kinds. As for thermosetting resins, there are no particular restrictions, and epoxy resins, phenolic resins, unsaturated polyester resins, vinyl ester resins, cyanate resins, polyimide resins, etc. can be cited. As for thermoplastic resins, there are no particular restrictions, and polyolefin resins, polyamide resins, polycarbonate resins, polyester resins, polyacetal resins, ABS resins, phenoxy resins, polymethyl methacrylate resins, polyphenylene sulfide resins, polyetherimide resins, polyether ketone resins, etc. can be cited. Among these, thermosetting resins are preferred, and epoxy resins and vinyl ester resins are more preferred, from the viewpoint of a higher adhesiveness-improving effect of the sizing agent of the present invention.
[0145] For the purpose of further improving the adhesiveness with the fiber bundle, these matrix resins may be partially or entirely modified.
[0146] The method for producing the fiber-reinforced composite material is not particularly limited, and known methods such as composite injection molding using chopped fibers or long fiber pellets, press molding using UD sheets or fabric sheets, and other filament winding molding can be used.
[0147] The content of the synthetic fiber bundle in the fiber-reinforced composite material is not particularly limited and can be appropriately selected depending on the type and form of the fiber, the type of the thermoplastic matrix resin, etc., and is preferably 5 to 70 wt %, more preferably 20 to 60 wt %, based on the obtained fiber-reinforced composite material.
[0148] Example
[0149] The present invention is specifically described below by way of examples, but is not limited to the examples described herein. It should be noted that the percentages (%) and parts shown in the following examples represent "weight %" and "weight parts" unless otherwise specified. The measurement of each characteristic value is performed based on the method shown below.
[0150] <Permeability Evaluation>
[0151] The permeability was evaluated by the following felt sedimentation test.
[0152] NIKKE woven felt S20 (No. 103) cut into 2 cm × 2 cm was floated on 100 mL of each sizing agent diluted with water to a non-volatile matter concentration of 1%, and the time (in seconds) until sedimentation was measured to evaluate the permeability. Temperature: 23°C. The shorter the time until sedimentation, the better the permeability.
[0153] The indicators are as follows, and ◎ and ○ are considered pass.
[0154] Very good (◎): 90 seconds or less
[0155] Good (○): More than 90 seconds and less than 180 seconds
[0156] Slightly poor (△): more than 180 seconds and less than 300 seconds
[0157] Bad (×): More than 300 seconds
[0158] <Adhesion rate of treatment agent>
[0159] About 10 g of the fiber to which the sizing agent composition had been applied was placed in a Soxhlet extractor and extracted with methyl ethyl ketone for 2 hours, and the weight was calculated based on the difference in the weight of the fiber before and after the extraction.
[0160] <Method for preparing matrix resin droplets>
[0161] Epoxy resin: Droplets of a matrix resin prepared to 100 parts by weight of epoxy resin jER828 (Mitsubishi Chemical Corporation) and 3 parts by weight of DICY (Mitsubishi Chemical Corporation) were formed on the carbon fiber filaments and heated and cured at 80°C for 1 hour and 150°C for 3 hours.
[0162] Polyamide resin: Polyamide resin T-663 (manufactured by Toyobo Co., Ltd.) was melted on a composite material interface property evaluation device HM410 (manufactured by Toei Sangyo Co., Ltd.) and formed into droplets on the carbon fiber filaments.
[0163] <Wettability of Matrix Resin>
[0164] The wettability of each matrix resin was evaluated using a composite material interface property evaluation device HM410 (manufactured by Toei Industry Co., Ltd.). Carbon fiber filaments were taken out from the carbon fiber tows obtained in the examples and comparative examples and installed on a sample holder. Droplets of the above-mentioned matrix resin were formed on the carbon fiber filaments, and 20 droplets with a droplet diameter in the pull-out direction ranging from 100 to 120 μm were selected to measure the contact angle relative to the carbon fiber filaments and obtain the average value. The contact angle was obtained in the same manner using carbon fiber filaments taken out from a carbon fiber tow that was not treated with a sizing agent, and compared. The wettability of each matrix resin was evaluated according to the following criteria, and ◎ and ○ were set as qualified.
[0165] ◎: The contact angle is 2° or more smaller than the contact angle of carbon fiber not treated with a sizing agent.
[0166] ○: The contact angle is smaller by 1° or more than the contact angle of carbon fiber not treated with a sizing agent.
[0167] △: The contact angle is almost the same as that of the carbon fiber not treated with sizing agent (the difference in contact angle is less than ±1°)
[0168] ×: The contact angle is larger by 1° or more than the contact angle of carbon fiber not treated with a sizing agent.
[0169] <Adhesion>
[0170] The adhesiveness was evaluated by a microdrop method using a composite material interface property evaluation device HM410 (manufactured by Toei Sangyo Co., Ltd.).
[0171] The carbon fiber filaments were taken out from the carbon fiber bundles obtained in the examples and comparative examples and installed in the sample holder. Droplets of each matrix resin were formed on the carbon fiber filaments to obtain a sample for measurement. The measurement sample was installed in the device, the droplets were clamped by the device scraper, and the carbon fiber filaments were moved on the device at a speed of 0.06 mm / min, and the maximum pull-out load F when the droplets were pulled out from the carbon fiber filaments was measured.
[0172] The interfacial shear strength τ was calculated by the following formula to evaluate the adhesion between the carbon fiber filaments and the matrix resin. The epoxy resin and polyamide resin described above were used as the matrix resin. Each matrix resin droplet was prepared by the method described above.
[0173] Interface shear strength τ (unit: MPa) = F / πdl
[0174] (F: maximum pull-out load, d: carbon fiber filament diameter, l: particle size of the droplet in the pull-out direction)
[0175] <Abrasion resistance>
[0176] Using a TM-200 friction entanglement force tester (manufactured by Daiei Kagaku Seiki Mfg. Co., Ltd.), the carbon fiber bundles obtained in the embodiments and comparative examples were rubbed 1000 times at a tension of 50 g (reciprocating motion speed of 300 times / minute) via three mirror chrome-plated stainless steel needles arranged in a serrated manner. The fuzzing state of the carbon fiber bundles was visually judged according to the following criteria, and ◎ and ○ were set as qualified.
[0177] ◎: The same as before rubbing, and no fuzzing was observed.
[0178] ○: Although some fluff was observed, it was a level that was completely acceptable in practical use.
[0179] △: Much fuzzing was observed, and some fiber breakage was confirmed.
[0180] ×: Many fuzzing and single-filament breakage were observed.
[0181] <Clustering>
[0182] Each sizing agent (diluted with water to 3%, target adhesion rate 1%) was applied to the carbon fiber, and 10 pieces of the carbon fiber were cut into 5 mm lengths with a cutter, and visual observation was performed to see if they were untied. The following evaluation criteria were used for judgment, and ◎ and ○ were considered acceptable.
[0183] ◎: Untie less than 2 pieces
[0184] ○: 3 to 4 untied
[0185] △: 5 to 7 untied
[0186] ×: 8 or more pieces untied
[0187] <Weight Average Molecular Weight and Number Average Molecular Weight>
[0188] In the present invention, the weight average molecular weight and the number average molecular weight are values measured by the following gel permeation chromatography (GPC) measurement method and obtained in terms of polystyrene.
[0189] (GPC measurement conditions)
[0190] Apparatus: Apparatus name: "HPLC LC-6A SYSTEM" (manufactured by SHIMAZU Co., Ltd.)
[0191] Column: "KF-800P (10mm×4.6mmφ)", "KF-804 (300mm×8mmφ)", "KF-802.5 (300mm×8mmφ)", "KF-801 (300mm×8mmφ)" (all manufactured by SHODEX)
[0192] Mobile phase: Tetrahydrofuran (THF)
[0193] Flow rate: 1.0ml / min
[0194] Sample volume: 100 μl (diluted 100 times)
[0195] Column temperature: 50°C
[0196] Standard material for making calibration curve: polystyrene (PSt)
[0197] The compounds used in the examples are as follows.
[0198] a1-1: jER828 / jER1001 = 50 / 50 (weight ratio) (epoxy resin mixture manufactured by Mitsubishi Chemical Corporation)
[0199] a1-2: Vinyl ester resin (bisphenol A diglycidyl ether acrylic acid adduct)
[0200] a1-3: Unsaturated polyester resin (synthesis example a1-3 below)
[0201] a1-4: jER807 / jER4005P = 50 / 50 (weight ratio) (epoxy resin mixture manufactured by Mitsubishi Chemical Corporation)
[0202] a1-5: Vinyl ester resin (trimethylolpropane trimethacrylate)
[0203] a1-6: Unsaturated polyester resin (synthesis example a1-6 below)
[0204] a2-1: Aromatic polyurethane resin (Synthesis Example a2-1 below)
[0205] a2-2: Saturated polyester resin (synthesis example a2-2 below)
[0206] a2-3: Polyolefin resin (maleic anhydride-modified polypropylene resin (propylene / maleic anhydride graft copolymerization ratio (weight %): 95 / 5, weight average molecular weight: 30,000))
[0207] a2-4: Aromatic polyurethane resin (Synthesis Example a2-4 below)
[0208] a2-5: Saturated polyester resin (synthesis example a2-5 below)
[0209] a2-6: Polyolefin resin (maleic anhydride-modified polypropylene resin (propylene / maleic anhydride graft copolymerization ratio (weight %): 85 / 15, weight average molecular weight: 37,000))
[0210] a3-1: KM-9749 (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0211] a3-2: SBL0533 (manufactured by ENEOS Materials Co., Ltd.)
[0212] a3-3: KM-2002-L-1 (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0213] a3-4: SBL0548 (manufactured by ENEOS Materials Co., Ltd.)
[0214] a'4: 2-ethylhexyl stearate
[0215] b1: 20 mol ethylene oxide adduct of 2,4,7,9-tetramethyl-5-decyne-4,7-diol
[0216] b2: 5 mole adduct of ethylene oxide to 2,4,7,9-tetramethyl-5-decyne-4,7-diol
[0217] b3: 3,6-dimethyl-4-octyne-3,6-diol
[0218] b4: 2,4,7,9-Tetramethyl-5-decyne-4,7-diol
[0219] c1: POEO block polyether (PO / EO=20 / 80) (M w 15500)
[0220] c2: POEO block polyether (PO / EO=50 / 50) (M w 4500)
[0221] In addition, a1-1, a1-2, a1-3, a1-4, a1-5, a1-6, a2-3, a2-6, a'4, b3 and b4 are non-self-emulsifying components.
[0222] (Synthesis example a1-3)
[0223] 0.9 mol of maleic anhydride and 1.0 mol of bisphenol A ethylene oxide adduct 4 mol were reacted at 140° C. for 5 hours to obtain an unsaturated polyester resin (a1-3) having an acid value of 2.5. w ) is 5051, and the weight average molecular weight (M w ) and number average molecular weight (M n ) ratio (M w / M n ) is 1.6.
[0224] (Synthesis example a1-6)
[0225] 0.8 mol of maleic anhydride and 1.0 mol of ethylene oxide adduct of bisphenol A were reacted at 140° C. for 3 hours to obtain an unsaturated polyester (a1-6) having an acid value of 3.5. w ) is 1626, and the weight average molecular weight (M w ) and number average molecular weight (M n ) ratio (M w / M n ) is 1.7.
[0226] (Synthesis Example a2-1)
[0227] While nitrogen was sealed in the reactor, 498 parts of terephthalic acid, 332 parts of isophthalic acid, 248 parts of ethylene glycol, 106 parts of diethylene glycol, 45 parts of tetramethylene glycol and 0.2 parts of dibutyltin oxide were added, and an esterification reaction was carried out at 190 to 240°C for 10 hours to obtain an aromatic polyester polyol. Next, 1000 parts of the obtained aromatic polyester polyol was dehydrated by reduced pressure at 120°C, cooled to 80°C, and 680 parts of methyl ethyl ketone were added and stirred to dissolve. Next, 218 parts of isophorone diisocyanate and 67 parts of 2,2-dimethylolpropionic acid as a chain elongating agent were added, and a urethanization reaction was carried out at 70°C for 12 hours. After the reaction was completed, it was cooled to 40°C, 97 parts of 13.6% ammonia water were added to neutralize the reaction, and then reduced pressure treatment was carried out at 65°C to distill off methyl ethyl ketone to obtain an aromatic polyurethane resin (a2-1).
[0228] (Synthesis Example a2-4)
[0229] While nitrogen was sealed in the reactor, 332 parts of terephthalic acid, 332 parts of isophthalic acid, 146 parts of adipic acid, 258 parts of ethylene glycol, 106 parts of diethylene glycol, 52 parts of neopentyl glycol and 0.2 parts of dibutyltin oxide were added, and an esterification reaction was carried out at 190 to 240°C for 10 hours to obtain an aromatic polyester polyol. Next, 1000 parts of the obtained aromatic polyester polyol was dehydrated by reduced pressure at 120°C, cooled to 80°C, and 680 parts of methyl ethyl ketone were added and stirred to dissolve. Next, 160 parts of hexamethylene diisocyanate and 67 parts of 2,2-dimethylolpropionic acid as a chain elongating agent were added, and a urethanization reaction was carried out at 70°C for 12 hours. After the reaction was completed, it was cooled to 40°C, 97 parts of 13.6% ammonia water were added for neutralization reaction, and then reduced pressure treatment was carried out at 65°C to distill off methyl ethyl ketone to obtain an aromatic polyurethane resin (a2-4).
[0230] (Synthesis Example a2-2)
[0231] While nitrogen was sealed in the reactor, 950 parts of dimethyl isophthalate, 1000 parts of diethylene glycol, 0.5 parts of zinc acetate and 0.5 parts of antimony trioxide were added and an ester exchange reaction was carried out at 140 to 220° C. for 3 hours. Subsequently, 30 parts of 5-sodium sulfoisophthalate was added and an esterification reaction was carried out at 220 to 260° C. for 1 hour, and then a polycondensation reaction was carried out at 240 to 270° C. under reduced pressure for 2 hours to obtain a saturated polyester resin (a2-2).
[0232] (Synthesis Example a2-5)
[0233] While nitrogen was sealed in the reactor, 475 parts of dimethyl isophthalate, 475 parts of dimethyl terephthalate, 1000 parts of diethylene glycol, 0.5 parts of zinc acetate and 0.5 parts of antimony trioxide were added and an ester exchange reaction was carried out at 140 to 220° C. for 3 hours. Subsequently, 30 parts of 5-sodium sulfoisophthalate was added and an esterification reaction was carried out at 220 to 260° C. for 1 hour, followed by a polycondensation reaction at 240 to 270° C. under reduced pressure for 2 hours, and then a polycondensation reaction was carried out at 240 to 270° C. under reduced pressure for 2 hours to obtain a saturated polyester resin (a2-5).
[0234] (Manufacture of sizing agents for fibers)
[0235] (Example 1)
[0236] 75 parts by weight of epoxy resin mixture a1-1 as a non-self-emulsifying component, 10 parts by weight of c1 and 10 parts by weight of c2 as an emulsifier were placed in an emulsifying device, and water was slowly added under stirring to perform phase inversion emulsification to obtain a uniform aqueous dispersion of the non-self-emulsifying component. Then, 5 parts by weight of b1 as the remaining component other than the non-self-emulsifying component and the emulsifier was mixed with the aqueous dispersion to obtain a sizing agent with a non-volatile matter concentration of 40% by weight.
[0237] (Examples 2 to 39 and Comparative Examples 1 to 14)
[0238] The components selected from a1-1, a1-2, a1-3, a1-4, a1-5, a1-6, a2-3, a2-6, a'4, b3 and b4 as non-self-emulsifying components, the components selected from c1 and c2 as emulsifiers, and the components selected from a2-1, a2-2, a2-4, a2-5, a3-1, a3-2, a3-3, a3-4, b1 and b2 as the remaining components other than the non-self-emulsifying components and the emulsifiers were respectively set to the non-volatile compositions described in Tables 1 to 6. Except for the above, the same operation as in Example 1 was carried out to obtain a sizing agent. It should be noted that the numerical values described in the table represent the weight ratio of each component (the non-volatile matter in the case of a water dispersion) in the non-volatile matter of the sizing agent.
[0239] (Manufacture of fiber tow with sizing agent attached)
[0240] The obtained sizing agent was diluted with water to prepare a sizing agent dilution liquid having a nonvolatile matter concentration of 3% by weight.
[0241] Next, a carbon fiber tow (fineness 800tex, number of filaments 12000) not treated with a sizing agent was dipped and impregnated in the prepared sizing agent dilution by the Dip Nip method, and then dried with hot air at 105°C for 15 minutes to obtain a carbon fiber tow treated with a sizing agent. The obtained carbon fiber tow treated with a sizing agent was used to evaluate the permeability, adhesion rate of the treatment agent, wettability of the matrix resin, adhesion, abrasion resistance, and bundling properties by the above method.
[0242]
[0243]
[0244]
[0245]
[0246]
[0247]
[0248] As can be seen from Tables 1 to 4, the sizing agent of the examples contains compound (A) and acetylene compound (B), and the weight ratio of the above compound (B) to the above compound (A) ((B) / (A)) is 0.0005 to 0.13. Therefore, it can impart excellent wettability with the matrix resin to the fiber and can be suitably used as a sizing agent.
[0249] On the other hand, as shown in Tables 5 and 6, the sizing agents of the comparative examples are those that do not contain the compound (B) (Comparative Examples 1 to 3), those that do not contain the compound (A) (Comparative Examples 4, 11, and 14), and those that do not have (B) / (A) in the range of 0.0005 to 0.13 (Comparative Examples 5 to 10, 12, and 13). As a result of the evaluation, in Comparative Examples 1 to 3, 5, 7, 9, 12, and 14, the wettability with the matrix resin is insufficient, and in Comparative Examples 4, 6, 8, 10, 11, and 13, although the wettability with the matrix resin is good, the bundling property is insufficient, and thus the requirements as a sizing agent are not satisfied. Therefore, any of the treatment agents of the comparative examples cannot be used as a fiber sizing agent for improving the wettability of the matrix resin with respect to the fiber bundle, and the subject of the present invention cannot be solved.
[0250] Industrial Applicability
[0251] Fiber-reinforced composite materials obtained by reinforcing a matrix resin with reinforcing fibers can be used for automotive applications, aerospace applications, sports and leisure applications, general industrial applications, etc. As reinforcing fibers, various inorganic fibers such as carbon fibers, glass fibers, and ceramic fibers, and various organic fibers such as aramid fibers, polyamide fibers, and polyethylene fibers can be cited.
Claims
1. A sizing agent for fibers, comprising a compound (A) and an acetylene compound (B), The compound (A) is at least one selected from a thermosetting resin (A1), a thermoplastic resin (A2) and a rubber (A3), The weight ratio of the acetylene compound (B) to the compound (A), ie, (B) / (A), is 0.0005 to 0.
13.
2. The fiber sizing agent according to claim 1, wherein The thermosetting resin (A1) is at least one selected from epoxy resin (A1-1), vinyl ester resin (A1-2) and unsaturated polyester resin (A1-3). The thermoplastic resin (A2) is at least one selected from an aromatic polyurethane resin (A2-1), a saturated polyester resin (A2-2) and a polyolefin resin (A2-3). The rubber (A3) is at least one selected from silicone rubber (A3-1) and diene rubber (A3-2). 3 . The fiber sizing agent according to claim 1 , further comprising a nonionic compound (C), wherein a weight ratio of the acetylene compound (B) to the nonionic compound (C), i.e., (B) / (C), is 0.001 to 0.
5.
4. The fiber sizing agent according to claim 3, wherein The weight average molecular weight of the nonionic compound (C) is 1,000 to 20,000.
5. The fiber sizing agent according to any one of claims 1 to 4, wherein The acetylene compound (B) is at least one selected from acetylene alcohol (B1), acetylene diol (B2), a compound (B3) obtained by adding alkylene oxide to acetylene alcohol, and a compound (B4) obtained by adding alkylene oxide to acetylene diol.
6. The fiber sizing agent according to claim 5, wherein The acetylene alcohol (B1) is a compound represented by the following general formula (1), the acetylene diol (B2) is a compound represented by the following general formula (2), the compound (B3) formed by adding alkylene oxide to acetylene alcohol is a compound represented by the following general formula (3), and the compound (B4) formed by adding alkylene oxide to acetylene diol is a compound represented by the following general formula (4), In formula (1), R 1 and R 2 are each independently an alkyl group having 1 to 8 carbon atoms, In formula (2), R 3 , R 4 , R 5 and R 6 are each independently an alkyl group having 1 to 8 carbon atoms, In formula (3), R 1 and R 2 are independently an alkyl group having 1 to 8 carbon atoms, R 7 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, AO represents an oxyalkylene group having 2 to 4 carbon atoms, and n is a number from 1 to 50, In formula (4), R 3 , R 4 , R 5 and R 6 are independently an alkyl group having 1 to 8 carbon atoms, R 7 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. It should be noted that the multiple R 7 They may be the same or different; AO represents an oxyalkylene group having 2 to 4 carbon atoms; and m and n are each independently a number of 1 to 50. 7 . A fiber bundle to which a sizing agent is attached, wherein the sizing agent for fibers according to claim 1 is attached to the fiber bundle.
8. A fiber-reinforced composite material comprising a matrix resin and the fiber bundle to which a sizing agent is attached according to claim 7.
9. The fiber-reinforced composite material according to claim 8, wherein: The matrix resin is at least one selected from a thermosetting resin and a thermoplastic resin.
Citation Information
Patent Citations
Surface treating resin composition for carbon fiber and composite carbon fiber material containing said treated fiber
JP1978052796A
Sizing agent composition for reinforcing fiber
JP1994173170A